Stability and erosion of the subcontinental lithospheric mantle : Relations between deformation, hydration and percolation of fluids and melts beneath the Kaapvaal craton and the East African Rift - (:unkn) unknown (My University, 2014)
This study provides additional constraints on the relations between deformation, hydration and percolation of fluids and melts in the subcontinental lithospheric mantle beneath a craton and a rift, as well as their implication on its geodynamical behaviour. I have analysed the microstructures, the CPOs, and the hydrogen content of mantle xenoliths from the Kaapvaal craton, and two sets of xenoliths from different localities along the East African Rift (North Tanzanian Divergence and SE Ethiopia).The coarse-granular microstructures and the well-defined CPOs in Kaapvaal peridotites suggest a deformation followed by a long quiescence time. Orthorhombic olivine CPOs predominates, but axial-[100] and axial-[010] are also measured. Cratonic peridotites record multiple metasomatic episodes, leading to a significant compositional heterogeneity, which cannot be imaged by seismic studies. Olivine hydrogen contents are variable, but tend to increase until 150 km depth, reaching up to 50 ppm wt. H2O. The deeper samples are almost dry. Piston-cylinder experiments on hydrogen diffusion between a volatile-rich kimberlitic melt and forsterite suggest that the presence of CO2 in the system could significantly decrease water fugacity and thus forsterite hydration. These experimental results indicate that the hydrogen contents measured in olivine were acquired during a metasomatic event rather than during xenolith extraction by kimberlites. However, this metasomatism was not followed by remobilization of the cratonic root.In the North Tanzanian Divergence, localities within the rift axis and the volcanic transverse belt (Lashaine and Olmani) show significant differences in microstructures and olivine CPO patterns. In Lashaine, coarse-granular microstructures and orthorhombic to axial-[100] CPO patterns in olivine can be explained by transpressional deformation during the formation of the Mozambique belt, or by the occurrence of a remnant of a cratonic domain embedded wit
Keywords: African Research